Respostas

2014-05-15T17:55:57-03:00
Utilize a fórmula de Bháskara:
X =  \frac{-b+- \sqrt{b^2-4ac(delta)} }{2a}

a) 16x^2-8x+1=0
Δ = (- 8)² - 4 . 16 . 1           
Δ = 64 - 64
Δ = 0

X =  \frac{- (-8)+- \sqrt{0} } {2.16} =  \frac{8}{32} ou (÷8) =  \frac{1}{4}

S = { \frac{1}{4} }

b) 4x^2-4x-35=0
Δ = (- 4)² - 4 . 4 . (- 35)
Δ = 16 + 560
Δ = 576

X =  \frac{- (-4)+-  \sqrt{576} }{2.4} =  \frac{4+-24}{8}

x' =  \frac{4+24}{8} =  \frac{28}{8} = 3,5 ou (÷ 4) =  \frac{7}{2}                 x" =  \frac{4-24}{8} =  \frac{-20}{8} = 2,5 ou (÷4) =  \frac{- 5}{2}

S = { \frac{7}{2} ,  \frac{-5}{2} }